Non-objective, two-dimensional, multi-planar space via line, form and color - Radding, Rosanna, author; Dietemann, David L., advisor; Orman, Jack L., committee member; Ellerby, David A., committee member; Yust, Dave, 1939-, committee member; Kilmer, Rosemary, committee member (Colorado State University. Libraries, 1979)
Transcendence of the inherent flat orientation of a two dimensional format and interrelation of opposites are the major objectives of my work. Visual references are extended through line, color and shape enabling one's eye to negotiate through, over and around shapes, both positive and negative, and to perceive the multi-level penetration of space. Line, color washes and calligraphic motifs in relation to the unprimed canvas on which they are painted break-up, dissolve and make fixed forms transparent for other forms lying behind them. The painting surface involves a multiplicity of moving form. The entirety is in motion seldom allowing the viewer to rest on any one visual point. The longer one looks the more one sees.
Zip file contains 20 slides of artist's works.
Keywords: Painting; Space (Art)